PLANKTONIC COMPOSITION OF DADIN KOWA DAM, GOMBE STATE, NIGERIA - BARA’ATU, A.; UMAR, D.M.; ABUBAKAR, K. A.; VANDI, P. (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY (2536-6041), 2019)
Planktons are small plants or animals that float, drift, or weakly swim in the water column. The organisms that constitutes this group are; phytoplanktons and zooplanktons. This paper presents the results of the variability in species composition and abundance of plankton in Dadin-Kowa Reservoir, Gombe State, Nigeria. Plankton was collected from three sites; sites A, B and C, these sites were water entry point, middle of the reservoir and the exiting point respectively, this was done to reduce bias in sampling. At each site a well labeled plastic bottles of 750 ml with full details of site of the sample and date of collection. Identification and counting of the phytoplankton and zooplankton sample was done using a compound microscope. The results showed a total of 16 species of phytoplankton belonging to four (4) different groups or classes which are Chlorophyceae, Cyanophycea, Bacillaroophycea, and Desmidiacea. The results showed a total of 10 species of zooplankton belonging to four (4) different groups or classes which are Protozoa, Rotifers, Copepodac and Cladorerans. In conclusion, the following phytoplanktons; Spirogyra Spp and Cyclotella Spp, and zooplanktons; Copepod Spp, Chlamydemonas Spp, Phacus Spp and Bosmina Spp were found to be dominant in Dadin-Kowa Dam.